Computer-Assisted Evaluation Of Bacterial Susceptibility Patterns To Antibiotic Usage In District Hospital - Yahaya, Ruhaiyem (1992)
A computer-based system developed using Dbase III Plus and Clipper Summer '87 runs on IBM PC/AT or its compatible was designed to assist in the evaluation of bacterial susceptibility pattern to antibiotic usage. 10,010 bacterial culture and sensitivity data from District Hospital Sungei Petani for the years 1986 to 1990 were processed by the system to study the susceptibility pattern of the various organisms isolated and then tested for correlation with antibiotic consumed during the five years.